2019
DOI: 10.1111/jth.14359
|View full text |Cite
|
Sign up to set email alerts
|

A computerized scoring system to improve assessment of heparin‐induced thrombocytopenia risk

Abstract: Current risk scores for heparin‐induced thrombocytopenia (HIT) are not computer‐friendly. We compared a new computerized risk score with the 4Ts score in a large healthcare system. The computerized risk score agrees with the 4Ts score 85% of the time. The new score could potentially improve HIT diagnosis via incorporation into decision support. Summary Background(HIT) is an immune‐mediated adverse drug event associated with life‐threatening thrombotic complications. The 4Ts score is widely used to estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…A HIT‐CR score was calculated every time a platelet count resulted in the EHR for inpatients receiving heparin products. The HIT‐CR score is based on the first two components of the 4Ts score including degree of thrombocytopenia and timing of the platelet count fall 10 . For thrombocytopenia, scores of 0, 1 and 2 are assigned to platelet count decreases from baseline of <30%, 30%–49% and ≥50%, respectively, with the baseline defined as the highest count recorded from <24 h before heparin initiation up to the time of the scoring.…”
Section: Methodsmentioning
confidence: 99%
“…A HIT‐CR score was calculated every time a platelet count resulted in the EHR for inpatients receiving heparin products. The HIT‐CR score is based on the first two components of the 4Ts score including degree of thrombocytopenia and timing of the platelet count fall 10 . For thrombocytopenia, scores of 0, 1 and 2 are assigned to platelet count decreases from baseline of <30%, 30%–49% and ≥50%, respectively, with the baseline defined as the highest count recorded from <24 h before heparin initiation up to the time of the scoring.…”
Section: Methodsmentioning
confidence: 99%
“…A maximal HIT‐CR score of 4 indicates that the 4Ts score is also at least 4, a threshold at which diagnostic testing would likely be recommended. Our previous study showed good agreement between HIT‐CR and 4Ts scores (κ = 0·69), and our statistical analysis indicated that the optimal mathematically derived cut‐off for a positive HIT‐CR score was a score of 3· 10 Using a cut‐off of 4 would improve the PPV at the cost of decreasing NPV. Whether this trade‐off would improve the clinical utility of HIT‐CR was uncertain as precise values for PPV and NPV were unknown.…”
Section: Introductionmentioning
confidence: 57%
“…The HIT computerised risk (HIT-CR) score is an automated short version of the 4Ts score that incorporates those elements of the 4Ts score stored as discrete data in most electronic health records. 10 The HIT-CR score assigns 0-2 points based on the degree of thrombocytopenia and 0-2 points based on the timing of onset of thrombocytopenia, for a total score of 0-4 points. A maximal HIT-CR score of 4 indicates that the 4Ts score is also at least 4, a threshold at which diagnostic testing would likely be recommended.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 , 15 HIT causes a potentially life-threatening hypercoagulable state with up to 50% of patients developing thromboembolic complications associated with a mortality rate of up to 30%. 12 , 16 , 17 The diagnosis of HIT usually requires a combination of both clinical features, laboratory testing with 4 T score and laboratory evaluation with heparin antibodies (PF4) and serotonin release assays (SRAs) being used. Treatment revolves around cessation of heparin products and use of alternative anticoagulation with parental direct thrombin inhibitors are used effectively to manage these cases until the platelet count rises back in approximately 3–7 days but it can take up to several weeks in refractory cases.…”
Section: Discussionmentioning
confidence: 99%